The poets of the first Islamic class in the hierarchy of distinguished poets - Al-Sadiq, Shuaib Idris (Al-Mukhtar Journal of Social Sciences, 2024)
The concept of the poetic "class" was an important critical issue in the thirteenth century, and Ibn Salim al-Jumahi was the first Arab critic to introduce this idea to the literary field. The first class in Arabic literature, consisting of Jarir, al-Farazdaq, al-Akhtal, and al-Ra’i al-Namiri, was classified as the finest poetic and critical category. Each poet had their own specific criteria for criticism, and their poetic strength and superiority in the field of poetry were evident through their artistic quality and excellence. Ibn Salim grouped them together in one class based on this quality.